Benefits from Kipsigis Women Engaging in Socio-Economic Activities in Kericho and Bomet Counties, Kenya - Ngeny, Elizabeth; Pappa, Marina (Journal of Philosophy, Culture and Religion, 2024)
Purpose: To investigate the impact of Kipsigis women group economic activities and how the public perceive this new undertaking in Kericho and Bomet Counties in Kenya. Methodology: The study used a qualitative research design, where different components of the study addressed the research problem. Probability sampling technique was used to select the participants in the study. The methods used to interrogate the participants included: focus group discussions, observation and face to face interviews. Each participant responded to the questions individually, as posed in the interview guide. This was later collected by the researcher for perusal and recording of the result that was compiled along with those from other methods. Along with the focus groups discussions, the researcher selected topics related to the topic of the study for discussion in the groups. The questions used in the different methods were posed to the participants who had been purposively selected to represent the rest of the population. This was done with the view of collecting the data that was later analyzed using tools such as NVivo or done manually. This study manually analyzed the data collected from the participants through the afore-mentioned research techniques for collecting the data. Findings: The findings showed that there was recognition of women’s contribution in society. The results from Bomet County indicated that 52% have embraced and supported women’s group activities, 24% see such group activities as making the women responsible and hardworking while another 24% feel that the women are not well supported in their group economic activities. In Kericho County, the results indicated that 54% felt that women’s contribution would improve living standards and another 46% felt that the group ability would significantly improve. The study also sought to find out the effect of women engaging in socio-economic activities on the home and family. The results from women in Kericho County show that 96% indicated that there was a positive effect on family and society as stated in the research outcome, 4% said there was no effect. The results from Bomet County showed that 98% of participants agreed that the women involvement in economic activities had a positive effect on family and society. Two percent were of the feeling that there was no effect on the home and family. Bomet had a percentage of respondents who indicated that women have not contributed much through their involvement in economic activities. Unique Contribution to Theory, Practice and Policy: The Critical Social Theory helps in understanding social functioning and behavior among gender groups in the society, where men and women roles among the Kipsigis is very distinct. Women assigned roles are undertaken by women and girls as their responsibilities lies in the kitchen and around the home. This is where the small children and the elderly are, and the women and the older girls are expected to undertake those roles without question.